New species of Leptohyphidae (Insecta: Ephemeroptera) from Colombia with evidence of reproductive time segregation - Molineri, Carlos (2006)
Five new species of Leptohyphidae are described, four of them from nymphal and adult stages: Leptohyphes albipennis, L. coconuco, L. nigripennis, and Tricorythodes trifasciatus. Tricorythopsis ticuna is described from male imagines only. Two of the new species, Leptohyphes albipennis and L. nigripennis represent a distinct group in the genus characterized by the presence of hind wings in the female and T-shaped penes in the male. Both species, very closely related, differ markedly in swarm time activity. SEM photographs of the eggs of L. nigripennis are presented.